THE IMPACT OF USING COMPUTERS ON STUDENTS' WRITING PERFOITMANCE - Hadriana Hadriana (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
The purposes of this study were to determine the impact of using computers on the quantity and quality of students' writing as rvell as the attitudes of the students torvard writing. The participants of this study were the first year students of Errglish Study' Program of FKIP Riau University. As the students learned the steps of the writing process, together with a partner they wrote a paragraph by using computers. The results of this study indicated that there were improvement of the students' writing performance in all components of writing. The students wrote better quality paragraph, wrote longer, and had a better overall attitude toward writing. The mean score of students'pretest was 53.93 and improved to 70,74 in the posttest.